Oxidative Annulation of 3‐Aryl‐2H‐benzo[e][1, 2, 4]thiadiazine‐1, 1‐dioxides with Aryl Aldehydes: An Easy Access to Hydroxyisoindolo[1, 2‐b] benzothiadiazinedioxide Scaffolds. Issue 8 (13th February 2020) - Kumar, G. Ravi; Banik, Swarnayu; Ramesh, Boora; Sridhar, Balasubramanian; Venkata Subba Reddy, Basireddy
Abstract : A novel and efficient approach has been developed for the synthesis of a diverse range of hydroxyisoindolo[1, 2‐ b ]benzothiadiazinedioxide derivatives through a sequential palladium catalyzed cross‐dehydrogenative coupling (CDC) and intramolecular cyclization. This method works not only with aryl aldehydes and alcohols but also with toluene to generate angularly fused heterocycles in good to excellent yields. Abstract : A novel strategy has been developed for the synthesis of hydroxyisoindolo[1, 2‐ b ] benzothiadiazinedioxide derivatives through a sequential cross‐dehydrogenative coupling (CDC) and intramolecular annulation. This method works not only with aryl aldehydes and alcohols but also with toluene to produce annulated products.